Does human oocyte cryopreservation affect equally on embryo chromosome aneuploidy? - Buderatska, Nataiia; Gontar, Juliia; Ilyn, Ihor; Petrushko, Maryna; Yurchuk, Taisiia (Cryobiology, 2020)
Oocytes cryopreservation is an important part of assisted reproduc tive technologies (ART) [12]. According to a new trend of delayed maternity, the oocytes and embryos are cryopreserved at early women reproductive age. Such an approach of fertility preservation permits to plan the most convenient life period for maternity, to accumulate oo cytes for women with low ovarian reserve, to treat infertility by ART with oocytes donation and to spare fertility in women undergoing gonadotoxic medical treatment [1,6,13]. In this regards, it is important to preserve not only morphological and functional characteristics of oocytes but either to keep intact their genetic apparatus. Oocytes’ meiotic spindle is very sensitive to the environmental changes and their microtubules gets depolymerize by slight temperature fluctuation [9, 15]. Meiotic apparatus disorders may cause an improper interaction between the oocyte chromosomes and as a result the number of aneu ploid embryos could be increased. Using a preimplantation genetic testing for aneuploidy (PGT-A) permits to select the embryos with a diploid chromosome number [14]. It has been reported that physical stress during oocyte vitrification affect the chromosome configuration and DNA integrity and suggested to determine the optimal condition, in particular, changing equilibration (up to 10 min) [8]. However, other authors reported that oocyte cryopreservation did not increase an aneuploidy in embryos, the implantation and live birth rates compared with the embryos derived from fresh oocytes cycles [7]. The aim of this work was to assess the impact of human oocytes cryopreservation on chromosomal status of preimplantation embryos.